2014
DOI: 10.1002/elps.201300527
|View full text |Cite
|
Sign up to set email alerts
|

Use of phytochemomics to evaluate the bioavailability and bioactivity of antioxidant peptides of soybean β‐conglycinin

Abstract: This research investigates how in vitro digestion contributes to the release of antioxidant peptides crypted in soybean β-conglycinin (7S) and its deglycosylated form (D7S). It also investigates the uptake of the bioactive peptides by human intestinal Caco-2 cells using a bicameral system, and their effect on the antioxidant cell defense. Phytochemomics is used as a tool for achieving this goal. The peptides are obtained by mimicking human physiological gastrointestinal digestion conditions. The antioxidant ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
40
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 29 publications
1
40
0
Order By: Relevance
“…Chen et al (1995) reported that this is a peptide with significant antioxidative activity, attributed to the presence of His residues in the amino acid sequence (Uchida & Kawakishi, 1992), especially the LLPHH sequence. This peptide was also identified in a recent study about the release of antioxidant peptides from beta-conglycinin (Amigo-Benavent et al, 2014), in which BIOPEP was also employed to look for bioactive peptide sequences.…”
Section: Identification Of Potential Bioactive Peptidesmentioning
confidence: 90%
“…Chen et al (1995) reported that this is a peptide with significant antioxidative activity, attributed to the presence of His residues in the amino acid sequence (Uchida & Kawakishi, 1992), especially the LLPHH sequence. This peptide was also identified in a recent study about the release of antioxidant peptides from beta-conglycinin (Amigo-Benavent et al, 2014), in which BIOPEP was also employed to look for bioactive peptide sequences.…”
Section: Identification Of Potential Bioactive Peptidesmentioning
confidence: 90%
“…Soy and its fermented products contribute lot of health benefits like anticholesterolaemic, hormonal disorders, antioxidative, and antitumor activities (Messina, Persky, Setchell, & Barnes, ). Several reports had suggested that the peptide content of soy‐fermented products is greater than that of unfermented soybeans (Amigo‐Benavent et al, ; Capriotti et al, ; Okamoto et al, ; Singh, Vij, & Hati, ). Another important biomolecule of soy, i.e., soy isoflavones have received extensive attention.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, lunasin has been shown to restrain the oxidative status caused by chemical agents in both intestinal Caco-2 and hepatic HepG2 cells, and to inhibit inflammation in cultured RAW 264.7 macrophages. [11][12][13][14][15] Park et al 16 reported that isolated lunasin, either synthetic or soybean-purified, is easily digested after 2 min incubation with simulated gastric or intestinal fluids. 3 Food-derived peptides are expected to exhibit their health beneficial properties after being orally taken.…”
Section: Introductionmentioning
confidence: 99%